The influence of signs of social class on compassionate responses to people in need - Callaghan, Bennett; Delgadillo, Quinton M.; Kraus, Michael W. (Frontiers in Psychology, 2022)
A field experiment (N = 4,536) examined how signs of social class influence compassionate responses to those in need. Pedestrians in two major cities in the USA were exposed to a target wearing symbols of relatively high or low social class who was requesting money to help the homeless. Compassionate responding was assessed by measuring the donation amount of the pedestrians walking past the target. Pedestrians gave more than twice (2.55 times) as much money to the target wearing higher-class symbols than they did to the one wearing lower-class symbols. A follow-up study (N = 504) exposed participants to images of the target wearing the same higher- or lower-class symbols and examined the antecedents of compassionate responding. Consistent with theorizing, higher-class symbols elicited perceptions of elevated competence, trustworthiness, similarity to the self, and perceived humanity compared to lower-class symbols. These results indicate that visible signs of social class influence judgments of others’ traits and attributes, as well as in decisions to respond compassionately to the needs of those who are suffering.